VIOLENCE AND DISCRIMINATION AGAINST TRANSGENDER COMMUNITY- A LEGAL REMEDIAL ANALYSIS - K.S. Gopalakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian subcontinent is known for its varied cultures and diversities, with respect to transgender community. The stereotype and conservative mindset of society inculcates many discrimination and violence against the transgender community without being aware that their gender is not their choice, but it is a vis-major (Act of God). Gender based violence in India have been very well documented and analyzed in various perspectives. Our legal system is well trained as to set of laws governing the violence against transgender and discrimination in our society. The paper is about the heinous violence faced by the transgender communities by highlighting the stereotypic violence against them and the domestic violence faced by transgender, which is an un-addressed factor. The research paper analyses transgender bullying and it develops a holistical framework for the improvising legal frameworks for addressing transgender based issues in India.